The Influence of Nurses Therapeutic Communication in the Dimensions of Positive and Supportive Attitudes on Patient Satisfaction in the Inpatient Unit of Massenrempulu General Hospital, Enrekang Regency - Primadianty, Indri; Ince Annisah Adawiyah Arifin; Syamsinar Jamal (Institut Teknologi Kesehatan Dan Sains Wiyata Husada Samarinda, 2024)
Communication plays a very important role in carrying out administrative processes and interactions between elements in a group or organization. Communication is a form of conveying messages between two or more people which are processed from the communicator or message giver to the communicant or message recipient with a specific service goal. The aim of this research is to determine the effect of The Influence of Nurses' Therapeutic Communication in the Dimensions of Positive Attitudes and Supportive Attitudes on Patient Satisfaction in the Inpatient Installation of Massenrempulu General Hospital, Enrekang Regency. The purpose of this research is to determine the influence of nurse therapy communication dimensions of positive attitudes and supportive attitudes on patient satisfaction in the inpatient installation of Massenrempulu Hospital, Enrekang Regency. The type of research used is quantitative research with a cross sectional study approach. The population in this study was 75 patients. The data analysis method uses univariate and bivariate tests with the chi-square correlation test. This research shows There is an influence of positive attitude dimensions and nurses' supportive attitude dimensions on patient satisfaction in the Massenrempulu General Hospital Inpatient Installation, Enrekang Regency.